The Role Of Talent Management In Improving Performance And Funding Of Non-Profit Organizations: A Case Study Of The Yogyakarta City Cultural Youth Forum - Latifah; Tasrim (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This research investigates the strategic position of talent management in enhancing the effectiveness and sustainability of funds for non-profit organizations, with a focus on a case study of the Cultural Youth Forum in Yogyakarta. The background of this research is based on the need to efficiently manage human resources in a voluntary organization focused on preserving local culture, at a time when youth participation is declining. The main objective of this research is to understand how talent management strategies can contribute to organizational sustainability, both internally (member performance and loyalty) and externally (sponsor attractiveness and funding sources). The method used is a qualitative approach with a case study, thru data collection from online questionnaire surveys, in-depth interviews with officers, members, alumni, and external partners, as well as documentation of activities. The analysis process was conducted using a thematic approach thru data reduction, coding, theme identification, and conclusion drawing. Research findings indicate that the recruitment process is considered transparent (87%), experiential training enhances members' abilities (82%), and retention strategies prioritizing comfort and social recognition are effective in maintaining loyalty (78%). The three main themes identified are: talent as a driver of the program, social recognition as a retention strategy, and member quality as a symbolic asset for the organization. Talent management has proven to play a crucial role in the smooth running of programs, increased participation, and strengthening the organization's reputation in the eyes of sponsors. The conclusion of this research emphasizes that talent management is an essential component in maintaining the effectiveness and sustainability of non-profit organizations, and needs to be developed thru a structured training system, inclusive reward strategies, and communication that highlights the quality of members as the core value for the organization.